(untitled) (St. Leonards, 1998)
Japan, Taiwan, South Korea, the ASEAN economies, Vietnam, Russia, China and the Overseas Chinese are all subject to this analysis, capturing the motivations and mechanisms which drive these diverse economies. While each society organises its economic activities according to its own internal logic and needs, the contributors ask whether there is any useful Asian economic model, a north-east or south-east Asian model, or none at all.
Keywords: Asia,Châu Á; Economic conditions,Điều kiện kinh tế